Intramolecular base-stabilised adducts of main group halides - Aldridge, S; Calder, R; Coombs, D; Jones, C; Steed, J; Coles, S; Hursthouse, M (2002)
The coordination chemistry of alkoxo and amido ligands bearing pendant nitrogen or sulfur donors has been developed to include examples of main group complexes. The structural implications of amido ligand coordination augmented by a tethered pyridyl base have been investigated for group 13 and 14 derivatives {[6-(Me3SiN)-2-Me-C5H3N]SnCl3 and [6-(Me3SiN)-2-Me-C5H3N]BBr2}. Furthermore, the scope, kinetics and mechanism of the synthesis of alkoxo and amido derivatives from trimethylsilyl substituted precursors have been investigated in depth. The methodology is found to be applicable to a range of ligand frameworks of varying flexibility, stabilised by one or two "tether" arms.